2015
DOI: 10.1038/cddis.2015.124
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy sensitizes malignant pleural mesothelioma cells to dual PI3K/mTOR inhibitors

Abstract: Malignant pleural mesothelioma (MPM) originates in most of the cases from chronic inflammation of the mesothelium due to exposure to asbestos fibers. Given the limited effect of chemotherapy, a big effort is being made to find new treatment options. The PI3K/mTOR pathway was reported to be upregulated in MPM. We tested the cell growth inhibition properties of two dual PI3K/mTOR inhibitors NVP-BEZ235 and GDC-0980 on 19 MPM cell lines. We could identify resistant and sensitive lines; however, there was no correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 68 publications
4
41
0
Order By: Relevance
“…Consistent with this observation, Manara et al showed that NVP-BEZ235 induced sarcoma stasis, by arresting cells in G1 phase of the cell cycle, without remarkable effects on apoptosis (13). It was postulated that autophagy induced by NVP-BEZ235 was a pro-survival mechanism which rendered tumor cells capable of anti-apoptosis surviving in the kinase inhibitor (25)(26)(27).…”
Section: Discussionsupporting
confidence: 50%
“…Consistent with this observation, Manara et al showed that NVP-BEZ235 induced sarcoma stasis, by arresting cells in G1 phase of the cell cycle, without remarkable effects on apoptosis (13). It was postulated that autophagy induced by NVP-BEZ235 was a pro-survival mechanism which rendered tumor cells capable of anti-apoptosis surviving in the kinase inhibitor (25)(26)(27).…”
Section: Discussionsupporting
confidence: 50%
“…Thus, we hypothesize that in BLCAb001, but not in BLCAb002, inhibition of PI3K may induce a feed-back upregulation of receptor tyrosine kinases and, consequently, re-induction of pAKT and sustained autophagy, as reported in other tumor systems [59]. Recent studies have shown activation of autophagy as one of the critical molecular alterations that limits the anti-tumor effects of PI3K/mTOR inhibitors [60]. Our RNAseq data showed BNIP3 and BCL11A upregulation, and ULK2, BAG1, RAB11FIP4 and BCLL14 downregulation in BLCAb001 tumors, mirroring the higher levels of LC3B I/II by Western blot analysis (Figure 5A and 5B).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy has been suggested to promote resistance to inhibitors of the PI3K pathway (24,43). CQ is being investigated as an autophagy inhibitor in both preclinical and clinical studies.…”
Section: Cq Treatment Blocks Autophagy Induced By Pi3k Inhibition Andmentioning
confidence: 99%
“…Thus, autophagy is an attractive therapeutic target for cancer. PI3K and mTOR inhibition can induce autophagy, and inhibition of autophagy enhances the growth-suppressive and apoptotic effects of PI3K/mTOR inhibition (22)(23)(24).…”
mentioning
confidence: 99%